Azienda Ospedaliero-Universitaria Meyer Relazione Clinico-Scientifica 2010 - Majer, Katalin; Sirianni, Luigi (Proceedings e report, 2012)
The Clinical-Scientific Report of the Meyer University Hospital is a precious tool for the sharing and dissemination of information that synthesises the method of working, the results and the paths for improvement to which particular efforts need to be devoted. It is therefore an evaluation tool aimed at both the interior and the exterior of the Hospital. It is a dynamic instrument, which ought to be refined in parallel with the improvements pursued by the Hospital itself.